Problems of Сultural Adaptation of European Jewish in Shanghai During World War II - K. O. Terentiev (Концепт: философия, религия, культура, 2020)
During World War II, the inhumane Nazi policy condemned millions of people to death. The National Socialist ideology having anti-Semitism as one of its pillars was consolidated during Hitler’s tenure in Germany, descending into taking the villainous crimes against humanity for granted. More than 18 thousand European Jewish emigrants arrived in Shanghai in the late 1930’s seeking refuge. No special permission to enter this multinational city was required and the local community provided all assistance to make their adaptation easy. Despite the cultural and linguistic differences between the local community and the refugees, the latter succeeded in adaptation, contributing to the city`s development. Quite quickly a model of adaptation to new political, economic and sociocultural conditions was found. Over time, however, the pressure and volatility of the policy of Japan, which occupied Shanghai in 1937, placed Jews in a difficult, unpredictable and dangerous position. The study reveals the concealed chapter of the history of the Holocaust describing the hardship of the Jewish population forced to emigrate to the other parts of the world to save their own lives from Nazi persecution. The name «Shanghai» has become a synonym of «salvation» for the participants of those events who have always gratefully remembered the hard, but life-saving years spent there. Along with the historical context, the cultural issue is considered in this study based on evaluation of the Jewish refugees’ assimilation in the Asian metropolis, analysis of the crosscultural interaction having arisen in the new communication space and the research on maintenance of the Jewish community’s fundamental values in an unfamiliar environment.